Civil War in the Southwest : Recollections of the Sibley Brigade - Thompson, Jerry D. (Book collections on Project MUSE., 2001)
Written "to set the record straight," these veterans' stories provide colorful accounts of the bloody battles of Valverde, Glorieta, and Peralta, as well as details fo the soldier's tragic and painful retreat back to Texas in the summer of 1862.